Structural, morphological and optical properties and solar cell applications of thioglycolic routed nano cobalt oxide material - S. Ambika; S. Gopinath; K. Saravanan; K. Sivakumar; C. Ragupathi; T. A. Sukantha (Energy Reports, 2019)
In this research, cobalt oxide produced by the hydrothermal method through the using thioglycolic acid (TGA) as the fuel is discussed in this paper. The produced cobalt oxide nanomaterials are characterized via X-ray diffraction analysis (XRD), high resolution scanning electron microscopy (HR-SEM), high resolution transmission electron microscopy (HR-TEM), diffuse reflectance spectroscopy (DRS). Additionally, as a possible promising application of the cobalt oxide based dye-sensitized solar cells (DSSCs) are successfully fabricated and the cell performances are evaluated. Solar cells have recently drawn a growing research interest due to their increasing power conversion efficiency, proper bandgap, high absorption coefficient and the earth abundant nature.
Keywords: 330; DSSC and nano; Hydrothermal; Morphology; Structure